COVID-19 alters human microbiomes: a meta-analysis - Reuben, Rine Christopher; Beugnon, Rémy; Jurburg, Stephanie D. (Frontiers in Cellular and Infection Microbiology, 2023)
The SARS-CoV-2 has infected a substantial portion of the world's population, and novel consequences of COVID-19 on the human body are continuously uncovered. The human microbiome plays an essential role to host health and wellbeing, and multiple studies targeting specific populations have reported altered microbiomes in SARS-CoV-2-infected patients.Given the global scale and massive incidence of COVID on the global population, determining whether the effects of COVID-19 on the human microbiome are consistent and generalizable across populations is essential. To this end, we performed a synthesis of human microbiome responses to COVID-19. We collected 16S rRNA gene amplicon sequence data from 11 studies sampling the oral and nasopharyngeal or gut microbiome of COVID-19 infected and uninfected subjects. Our synthesis included 1,159 respiratory (oral and nasopharyngeal) microbiome samples and 267 gut microbiome samples from patients in 11 cities across four countries. Our reanalyses reveal communitywide alterations in the respiratory and gut microbiomes across human populations. We find significant overall reductions in the gut microbial diversity of COVID-19 infected patients, but not in the respiratory microbiome. Furthermore, we find more consistent community shifts in the gut microbiomes of infected patients than in the respiratory microbiomes, although the microbiomes in both sites exhibited higher host-to-host variation in infected patients. In respiratory microbiomes, COVID-19 infection resulted in an increase in the relative abundance of potentially pathogenic bacteria, including Mycoplasma. Our findings 2 highlight the need for further research into the long-term effects of COVID-19 on the human microbiome across populations, and the potential impact of these microbiome alterations on patient recovery.